Evaluating Fuzzy Reliability System using Intuitionistic Fuzzy Set (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
this paper a fuzzy  reliability  of a different types of a systems is calculated by using a reduction  method to series system and applying Intuitionistic rules of fuzzy  Sets which deals with uncertainty and incomplete informations to calculate the fuzzy reliability via illustrative example is presented with conclusions.